2003
DOI: 10.1167/iovs.03-0131
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Fibrils Appear More Closely Packed in the Prepupillary Cornea: Optical and Biomechanical Implications

Abstract: Collagen fibrils in the prepupillary cornea appear to be more closely packed than in the peripheral cornea. Anisotropy in fibril packing across the cornea has potential implications for the transparency and refractive index of the tissue. Biomechanically, it is possible that the higher packing density of stress-bearing collagen fibrils in the prepupillary cornea is necessary for maintaining corneal strength, and hence curvature, in a region of reduced tissue thickness. By inference, these results could have im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
146
0
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(173 citation statements)
references
References 29 publications
16
146
0
8
Order By: Relevance
“…Collagen fibril diameter in the affected infero-nasal quadrant of the failed-graft cornea did not differ significantly from that measured elsewhere within the same tissue or from those of other normal and unscarred keratoconus corneas, 15,21 suggesting that scar tissue (which has a larger fibril diameter) 22 was not present. However, it must be remembered that X-ray scattering data provide an average measurement of fibril diameters throughout the entire thickness of the cornea at the point through which the beam passes.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Collagen fibril diameter in the affected infero-nasal quadrant of the failed-graft cornea did not differ significantly from that measured elsewhere within the same tissue or from those of other normal and unscarred keratoconus corneas, 15,21 suggesting that scar tissue (which has a larger fibril diameter) 22 was not present. However, it must be remembered that X-ray scattering data provide an average measurement of fibril diameters throughout the entire thickness of the cornea at the point through which the beam passes.…”
Section: Discussionmentioning
confidence: 74%
“…Although the average fibril diameter in the failed-graft button was higher than that of the normal cornea (Po0.001), they were both within the typical range for healthy human corneas. 15 The variation in fibril diameters across the cornea was consistent for both the normal and failed-graft tissue.…”
Section: Fibril Diametermentioning
confidence: 68%
See 2 more Smart Citations
“…Kampmeier [45] found that porcine corneas were stiffer along the IS axis than the NT axis, which is consistent with the present observations where the effect was much less pronounced. Wide angle x-ray scattering experiments [13] on human corneas were unable to statistically distinguish fibril densities in the NT and IS direction, although they did show a dramatic reduction in fibril densities at 45…”
Section: Discussionmentioning
confidence: 93%